Survey of ICT and Education in Africa : Ghana Country Report - Mangesi, Kofi (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev)-supported survey of Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Ghana is in the process of finalizing its ICTs in education policy, due to be ready by the end of the first quarter of 2007. Despite the uncoordinated approach to policy in the past, significant progress has been made in increasing access to and usage of ICTs in the education sector. The tertiary sector is the most advanced in ICT deployment, followed by the secondary and primary/basic education sectors respectively. Overall there is much optimism for huge advances once the policy implementation begins.